CALCUPROB An on-line interactive calculator of probabilities - Fernández-Morales, Antonio (My University, 2012)
CalcuProb is an interactive open access on-line calculator for calculating critical values and probabilities from the most common probability distribution models.
Keywords: Critical values; Probability models; On-line calculator